Comparison of Intraocular Pressure Measurement by iCare Tonometer and Goldman Applanation Tonometer - Hameed, Asem; Saleem, Beenish; Mahwish Akhtar; Yousaf, Waseem; Khan, Taimoor Ashraf; Qadir, Abdul (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare the Intraocular Pressure measured by the Goldmann Applanation tonometer with by iCare ic100 tonometer in normal human eye to determine the accuracy and reliability of both methods. Study Design: Comparative cross-sectional study.Place and Duration of Study: Ophthalmology Department, Combined Military Hospital, Quetta Pakistan, from Oct 2022 to Apr 2023.Methodology: Approval was secured prior to enrolling every individual, protecting their privacy throughout the process. All instruments adhered to the manufacturer's guidelines for calibration. A single ophthalmologist assessed the intraocular pressure of all participants. In our study we included 400 eyes (200 right and 200 left) among 200 patients. Initially, study eyes were inspected using a slit lamp. Subsequently, iCare tonometer and Goldman applanation tonometer were employed to gauge the intraocular pressure.Results: Out of 200, 87 patients (43.5%) were male and 113(56.5%) were females. Median age of the patients was 51.00(45-58) years range from 22-77 years. Mean IOP measured by iCare was 19.01±7.86 mmHg and by Goldman applanation tonomter was 20.14±8.15 mmHg. The correlation coefficient value between the readings of two instruments was r=0.866 with significant p value (p< 0.001).Conclusion: The iCare ic100 consistently provides high intraocular pressure measurements (2-3mmHg) compared to the Goldmann Applanation tonometer across various sub Groups.